Who Counts? Ghanaian Academic Publishing and Global Science - Mills, David (African Minds, 2023)
Since the 1990s, global academic publishing has been transformed by digitisation, consolidation and the rise of the internet. The data produced by commercially owned citation indexes increasingly defines legitimate academic knowledge. Publication in prestigious 'high impact' journals can be traded for academic promotion, tenure and job-security. African researchers and publishers labour in the shadows of a global knowledge system dominated by 'Northern' journals and by global publishing conglomerates. This book goes beyond the numbers. It tells the story of how the Ghanaian academy is being transformed by this bibliometric economy. It offers a rich account of the voices and perspectives of Ghanaian academics and African journal publishers. How, where and when are Ghana's researchers disseminating their work, and what do these experiences reveal about an unequal global science system? Is there pressure to publish in 'reputable' international journals, what role do supervisors, collaborators and mentors play, and how do academics manage in conditions of scarcity? Putting the insights of more than 40 Ghanaian academics into dialogue with journal editors and publishers from across the continent, the book highlights creative responses, along with the emergence of new regional research ecosystems. This is an important Africa-centred analysis of Anglophone academic publishing on the continent and its relationship to global science.